Aromatic plants from Vetnam, sources of natural products for industry - Hoi, Tran Minh; Thai, Tran Huy; Bighelli, Ange; Casanova, Joseph (Academia Journal of Biology, 2014)
aromatic plants produce by vapour distillation or other processes essential oils which are products with high commercial value used in the natural product industries such flavour and fragrance, perfumes and cosmetics industries as well as pharmaceutical industry. The aim of this study was to characterise some aromatic plants from Vietnam through the chemical composition of their essential oils. We got interested in essential oils which contained a main component with high to ultra high content, susceptible to find an industrial use. For this study, a dozen of plants have been selected. The composition of their essential oils will be compared with those of the same plants, reported in the literature, from Vietnamese origin or from other countries.